Cyclical dimensions of labour mobility after EU enlargement - Alan Ahearnea; Herbert Brücker; Zsolt Darvasa; Jakob von Weizsäcker (Bruegel, 2009)
This paper explores the influence of the economic cycle on labour mobility within the EU, focusing on the likely impact of the present economic crisis. To do so, we use an econometrically calibrated simulation and a case study of Ireland. We find that, in the short run, the crisis is likely to lead to a somewhat lower stock of migrants from the new member states in the EU15 than would have been the case without the crisis on account of diminished job opportunities for migrants. By contrast, in the longer run the crisis might lead to a moderate increase in migration from some of the new member states compared to what would have been the case without the crisis. The latter is driven by the observation that the crisis may have undermined the economic growth model of some of the new member states, thereby slowing down their economic catching-up process.
Keywords: F22; C33; J61; O11; O15; O24; 330; labour mobility; economic cycle; crisis; European Union; Arbeitsmigration; Konjunktur; EU-Erweiterung; Wirtschaftskrise; Panel; Regression; Simulation; EU-Staaten; Irland